Formation and wear peculiarities of multilayer wear - resistant ZrB2 - containing spark and laser-spark coatings on titanium alloy - Подчерняева, И.А.; Панашенко, В.М.; Духота, А.И.; Панасюк, А.Д.; Костенко, А.Д. (Problems of Tribology, 2014)
Multilayer wear-resistant coating on VT3-1 titanium alloy was deposited by electric spark method. The coating was formed by alternation of alloying electrodes of NIAT-5 steel and ZrB2-containig ceramic. Formation of strong adhesion between layers in the coating was shown. From microprobe analysis of elements distribution across layers, it was a supposition that irregular transfer of Fe and Ti across the coating layers was determined by the interaction intensity of the elements with main phases of the layers. As compared with WC+3%Co ESD coating, wear resistance of multilayer ESD coating under fretting in air increased by 40%, and after its following laser melting – by 70%. The results are discussed within the framework of tribooxidation concept.